Pengaruh Blended Problem Based Learning Berbasis Google Classroom Terhadap Beban Kognitif Peserta Didik pada Materi Keanekaragaman Hayati - Nida Chairul Ummah; Romy Faisal Mustofa; Dea Diella (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2022)
This study aims to determine the effect of blended problem based learning based on google classroom on the cognitive load of students in class X MIPA. The sample was taken using a total sampling technique so that the entire population was sampled, while for determining the treatment of the sample used cluster random sampling technique. Class X MIPA 1 as many as 31 students as the experimental class and class X MIPA 2 as many as 30 students as the control class. The data analysis technique used is independent t test. Based on the results of data analysis and hypothesis testing, it can be concluded that there is an effect of blended problem based learning based on google classroom on cognitive load with a significance value of 0.013. The cognitive load of the students showed an average score of 3,233 with the category of low cognitive load.Penelitian ini bertujuan untuk mengetahui pengaruh blended problem based learning berbasis google classroom terhadap beban kognitif peserta didik di kelas X MIPA. Sampel diambil dengan teknik sampling total sehingga seluruh populasi dijadikan sampel sedangkan untuk penentuan perlakuan pada sampel digunakan teknik cluster random sampling. Kelas X MIPA 1 sebanyak 31 orang peserta didik sebagai kelas eksperimen dan kelas X MIPA 2 sebanyak 30 orang peserta didik sebagai kelas kontrol. Teknik analisis data yang digunakan yaitu uji t independent. Berdasarkan hasil analisis data dan uji hipotesis maka dapat disimpulkan bahwa ada pengaruh blended problem based learning berbasis google classroom terhadap beban kognitif dengan nilai signifikansi 0,013. Beban kognitif peserta didik menunjukkan rata-rata skor sebesar 3,233 dengan kategori beban kognitif rendah.Kata kunci: blended problem based learning, beban kognitif, eksperimen DOI: http://dx.doi.org/10.23960/jbt.v10i1.23890